2009
DOI: 10.1016/j.physletb.2009.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Dirac equation in noncommutative space for hydrogen atom

Abstract: We consider the energy levels of a hydrogen-like atom in the framework of θmodified, due to space noncommutativity, Dirac equation with Coulomb field. It is shown that on the noncommutative (NC) space the degeneracy of the levels 2S 1/2 , 2P 1/2 and 2P 3/2 is lifted completely, such that new transition channels are allowed.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
72
1
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(81 citation statements)
references
References 9 publications
2
72
1
6
Order By: Relevance
“…From now on, we put = c = 1 and, consequently, g = e. For the proton, by taking the charge radius of 0.9 fm for a we conclude that the correction to the magnetic moment is below the experimental error of 2.3 · 10 −8 µ N [17] already for Λ NC ≃ 0.24 TeV. An estimate of the NC proton magnetic moment contribution into the hyperfine splitting of the energy states in a hydrogen atom, based on a NC theory [8,18] of electron spectrum, does not strengthen the bound on l found in [6] with the use of the non-dipole magnetic solution given as eq. (13) below.…”
mentioning
confidence: 78%
“…From now on, we put = c = 1 and, consequently, g = e. For the proton, by taking the charge radius of 0.9 fm for a we conclude that the correction to the magnetic moment is below the experimental error of 2.3 · 10 −8 µ N [17] already for Λ NC ≃ 0.24 TeV. An estimate of the NC proton magnetic moment contribution into the hyperfine splitting of the energy states in a hydrogen atom, based on a NC theory [8,18] of electron spectrum, does not strengthen the bound on l found in [6] with the use of the non-dipole magnetic solution given as eq. (13) below.…”
mentioning
confidence: 78%
“…In terms of commutative variables ( , ), we find that the dynamical equation for component 1 takes the same form as (33). The corresponding Hamiltonian (34) in terms of commutative variables becomes…”
Section: Spin-0 and Spin-1 Bosons On Noncommutative Planementioning
confidence: 94%
“…Nonrelativistic noncommutative quantum mechanical models, such as noncommutative harmonic oscillator and noncommutative Landau problem, have been studied extensively [26][27][28][29][30][31][32]. The relativistic quantum mechanical models on noncommutative space are investigated since the work of [33]. Some geometrical phases in noncommutative relativistic quantum theory are studied in [34][35][36] recently.…”
Section: Introductionmentioning
confidence: 99%
“…Non-relativistic noncommutative quantum mechanics, such as noncommutative harmonic oscillator, noncommutative Landau problem have also been studied extensively [17][18][19][20][21][22][23]. The relativistic quantum mechanical models on noncommutative space are also investigated since the work of [24]. Interestingly, it is found that the noncommutativity even has a profound relationship with JC model in quantum optics context [25].…”
Section: (ē−E0)mentioning
confidence: 99%